Debt Management Performance Assessment : Armenia - World Bank (World Bank, Washington, DC, 2014)
The World Bank mission team comprised of Memes/ Messrs. Lilia Razlog (mission lead, PRMED, WB), Antonio Velandia (FABDM) and Ying Li (Consultant, WB), joined by Juan Carlos Vilanova, Debt Relief International (DRI), who conducted a Government Debt Management performance Assessment (DeMPA) evaluation for Republic of Armenia. At the request of the authorities, the mission took place from October 29 to November 8, 2013. The team worked closely with the main counterparts at the Ministry of Finance (MoF), NASDAQ-OMX, Chamber of Control (CoC), as well as the officials from the other government agencies and the Central Bank of Armenia (CBA). The mission team benefited from excellent cooperation of the Public Debt Management Department (PDMD) of the Ministry of Finance, other line departments of the MoF, CBA, Ministry of Justice, and other government and private partners.